1981
DOI: 10.1080/15287398109530028
|View full text |Cite
|
Sign up to set email alerts
|

Spleen changes in animals inhaling ambient levels of nitrogen dioxide

Abstract: The effects of ambient levels of NO2 on the spleens of adult and newborn Swiss Webster (S/W) mice were determined. Spleens were evaluated by the following criteria: (1) spleen weight, expressed as a percent of the body weight (% spleen weight), (2) size of the spleen lymphoid nodules as determined by computed image analysis, (3) spleen cell counts, and (4) histopathologic evaluation. Data for NO2-exposed animals were compared with data for control animals that inhaled filtered air. Totals of 217 control and 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1982
1982
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Some of our own data generated from studies pertaining to the spleen may be relevant to the mechanisms involved, since we have observed different spleen responses in the early and late phases of NO2 exposures (30,31). The latter observations considered together with other immunological studies which suggested immune stimulation in the early phases and suppression in the late phases of NO2 exposure (18) may be part of the mechanisms involved in the facilitation of metastases development.…”
mentioning
confidence: 89%
“…Some of our own data generated from studies pertaining to the spleen may be relevant to the mechanisms involved, since we have observed different spleen responses in the early and late phases of NO2 exposures (30,31). The latter observations considered together with other immunological studies which suggested immune stimulation in the early phases and suppression in the late phases of NO2 exposure (18) may be part of the mechanisms involved in the facilitation of metastases development.…”
mentioning
confidence: 89%
“…The spleen is the largest lymphatic organ of the immune system and plays a prominent role in host immune responses (Kuraitis et al 1981). Macrophages, as a part of the mononuclear phagocytic system ensuring non-specific and specific resistance of the organism, form one of the most important cellular mechanisms of protection against the harmful effects of environmental factors including chemical contaminants.…”
mentioning
confidence: 99%